The role of PPARγ in cancer cachexia: friend or foe? - Ding, Leili; Jiang, Hao; Shen, Liang; Xu, Yiming (Frontiers in Endocrinology, 2025)
Cachexia remains a major complication in cancer, with limited therapeutic options. Peroxisome proliferator-activated receptor gamma (PPARγ) has emerged as a key regulator of adipogenesis, lipid metabolism, and inflammation, but its role in cachexia is paradoxical. PPARγ activation can promote lipid storage, suppress inflammation, and modulate muscle–adipose crosstalk, potentially alleviating tissue wasting. Conversely, PPARγ agonists may enhance tumor growth in certain cancers, raising safety concerns. This review examines the dual functions of PPARγ in cancer cachexia, focusing on its regulation of adipose tissue remodeling (including browning and lipid metabolism), skeletal muscle homeostasis, and systemic inflammation, alongside tumor-promoting mechanisms that complicate its therapeutic use. Finally, emerging approaches such as selective PPARγ modulators (SPPARγMs) and tissue-targeted strategies are discussed to maximize anti-cachectic effects while minimizing oncogenic risks. Understanding these context-dependent actions is essential for translating PPARγ modulation into safe, effective cachexia therapies.